PENGARUH PUPUK ORGANIK DAN JARAK TANAM TERHADAP PRODUKSI TANAMAN KACANG TANAH (Arachis hypogaea L.) DI AGRO EKOSISTEM LAHAN RAWA - Gusmiatun Gusmiatun; Neni Marlina (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
Effect of Organic Fertilizer and Planting Distance on Peanut (Arachis hypogaea L.) Production in Swamp Agroecosystem.  Increasing the production of peanuts (Arachis hypogaea L.) in swamps can be done by applying cultivation technology, including using liquid organic fertilizer and adjusting the spacing. The purpose of this study was to determine the effect of several types of liquid organic fertilizer and plant spacing on peanut crop production and to determine which type of liquid organic fertilizer had the best effect on increasing peanut production in swamps. The layout of the plants in the field was arranged based on the Split Plot Design. Plot size 1.5 m x 2.0 m. As the main plot is liquid organic fertilizer (O), namely O0: control (chemical fertilizer), O1: liquid organic fertilizer of Lamtoro leaves, O2: liquid organic fertilizer of cow urine, O3: liquid organic fertilizer of tofu waste. The subplot is the planting distance (J), consisting of J1: 20 cm x 20 cm, J2 : 20 cm x 30 cm,J3: 15cm x 40cm. The variables observed were the number of primary branches, the total number of pods/plant, number of empty pods/plant, the weight of pods/plant, the weight of 100 seeds (g), and the weight of pods/harvest plot. The results indicated that Liquid organic fertilizer from tofu waste can give better results than liquid organic fertilizer from cow urine and Lamtoro leaves in increasing peanut production in swamps. Liquid fertilizer tofu waste can increase the production of dry pods by 23.98% compared to chemical fertilizers, which can produce 2.585 tons/ha. Cow urine liquid fertilizer can produce 2.295 tons/ha of dry pods, and Lamtoro leaf liquid fertilizer can produce 2.280 tons/ha of dry pods. The application of the right spacing can increase the production of peanuts in swamps, with a spacing of 15 cm x 40 cm (2.62 tons/ha). The production can increase by 25.42% when compared to a spacing of 20 cm x 20 cm (2.09 tons/ha).Keywords: Plant distance, peanuts, organic waste, swamp land                                                  ABSTRAK Peningkatan produksi kacang tanah (Arachis hypogaea L.) di lahan rawa dapat dilakukan dengan menerapkan teknologi budidaya, diantaranya menggunakan pupuk organik cair serta mengatur jarak tanam. Tujuan penelitian ini untuk mengetahui pengaruh beberapa jenis pupuk organik cair dan jarak tanam terhadap produksi tanaman kacang tanah serta untuk mengetahui jenis pupuk organik cair yang pengaruhnya paling baik dalam meningkatkan produksi kacang tanah di lahan rawa.  Tata letak tanaman di lapang disusun berdasarkan Rancangan Petak Terbagi (Split Plot Design).  Luas plot 1,5 m x 2,0 m. Sebagai petak utama adalah pupuk organik cair (O), yaitu O0: kontrol (pupuk kimia), O1: pupuk organik cair daun lamtoro, O2: pupuk organik cair urin sapi, O3: pupuk organik cair limbah tahu. Anak petak adalah jarak tanam (J), terdiri dari J1: 20 cm x 20 cm, J2: 20 cm x 30 cm, J3: 15 cm x 40 cm. Peubah yang diamati yaitu jumlah cabang primer, jumlah polong total/tanaman, jumlah polong hampa/tanaman, berat polong/tanaman, berat 100 biji (g), dan berat polong/petak panen.  Hasil penelitian menunjukkan bahwa pupuk organik cair dari limbah tahu dapat memberikan hasil yang lebih baik dibandingkan dengan pupuk organik cair dari urin sapi maupun daun Lamtoro dalam meningkatkan produksi kacang tanah di lahan rawa.  Pupuk cair limbah tahu dapat meningkatkan produksi polong kering sebesar 23,98% dibandingkan pupuk kimia, yaitu menghasilkan 2,585 ton/ha. Pupuk cair urin sapi dapat menghasilkan polong kering 2,295 ton/ha, dan pupuk cair daun Lamoro dapat menghasilkan polong kering 2,280 ton/ha. Penerapan jarak tanam yang tepat dapat meningkatkan produksi tanaman kacang tanah di lahan rawa, dengan jarak tanam 15 cm x 40 cm (2,62 ton/ha). Produksi meningkat 25,42% jika dibandingkan dengan jarak tanam 20 cm x 20 cm (2,09 ton/ha). Kata kunci: jarak tanam, kacang tanah, limbah organik, lahan rawa